Features of the motor function of the gastrointestinal tract at the cross-functional pathology - Alla E. Lychkova; Aleksey A. Samsonov; Dmitry N. Andreev; Elena I. Kuznetsova (ZAO "Consilium Medicum", 2023)
Aim. To identify the role of impaired motor function of the gastrointestinal tract (GIT) in the overlap of functional disorders (FD). Materials and methods. Thirty-two abdominal FD patients were followed up, with a predominance of women aged 33.76.1 years (75%). Men aged 31.85.6 years were 25%. All patients had symptoms of GIT FD established according to the Rome IV criteria, endoscopy, and abdominal ultrasound. In addition, patients underwent 2-hour pH-metry and electromyography of the abdominal organs using bipolar silver electrodes with a surface area of 0.50.6 cm2. The amplitude-frequency characteristics of slow waves and spikes and the power of phase and tonic contractions were analyzed using the Canon M hardware and software complex with a transmission frequency of 0.1 to 10 Hz and a noise level of 15 W. Results. Overlapping clinical symptoms of motor disorders in gastrointestinal tract functional disorders are observed at a young age, mainly in women. The abnormal ratio of the gallbladder and common bile duct motility in overlapping GIT FD was 1:1.08, with a pronounced increase in contractions of the common bile duct, which could lead to an increase in pressure in the biliary system, pain, and insufficient flow of bile to the duodenum, disrupting the digestion and worsening the dyspepsia. Conclusion. The study showed a tendency for higher incidence of functional disorders in young women. Patients with overlapping disorders also have more severe pain than those with isolated disorders.